2008
DOI: 10.1074/jbc.m805545200
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulates Both JAK2-dependent and JAK2-independent Signaling Pathways

Abstract: Leptin, an adipocyte-derived hormone, controls energy balance and body weight via its long form receptor LEPRb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 45 publications
3
72
1
2
Order By: Relevance
“…Moreover, in studies with human breast carcinoma cells, it was shown that Stat-3 can not only be activated via the classical JAK/Stat-pathway, but also by src kinases, because an inhibition of these tyrosine kinases was accompanied by a dose-dependent blocking of Stat-3 signaling (Garcia et al 2001). Src-specific inhibitors such as pp2 significantly attenuated leptinstimulated tyrosine phosphorylation of Stat-3 in both fibroblast and neurons (Jiang et al 2008). We can approve this correlation, because incubation of the cells with leptin in combination with pp2, resulted in a significant decrease of Stat-3 activation (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, in studies with human breast carcinoma cells, it was shown that Stat-3 can not only be activated via the classical JAK/Stat-pathway, but also by src kinases, because an inhibition of these tyrosine kinases was accompanied by a dose-dependent blocking of Stat-3 signaling (Garcia et al 2001). Src-specific inhibitors such as pp2 significantly attenuated leptinstimulated tyrosine phosphorylation of Stat-3 in both fibroblast and neurons (Jiang et al 2008). We can approve this correlation, because incubation of the cells with leptin in combination with pp2, resulted in a significant decrease of Stat-3 activation (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…LepRb cells were cultured in F-12K medium with 12% horse serum and 3% fetal bovine serum (20). Cells were fixed by 4% PFA for 5 to 10 min.…”
Section: Generation Of Shp2mentioning
confidence: 99%
“…Leptin is the key signaling molecule responsible for long term satiety and energy balance; mutations that cause defective leptin secretion or abnormal leptin receptor signaling result in obesity in ob/ob mice (9, 10) and in humans (11). The leptin receptor belongs to the IL-6 receptor family of class 1 cytokine receptors and mediates the biological effects of leptin via the Janus kinase 2-signal transducer and activator of transcription 3 (JAK2/STAT3) pathway (12)(13)(14). Several splice variants of the leptin receptor exist; however, the LRb isoform mediates the leptin effect on satiety (4).…”
mentioning
confidence: 99%